Controle autonômico do coração e fração de ejeção na fase crônica do acidente vascular encefálico - Vieira, Suenimeire (2014)
Introduction:Subjects affected by cerebrovascular accident (CVA) may show changes in the structure and function of the heart and autonomic modulation.Objective:To assessautonomic and cardiac systolic function in men after stroke, and whether these variables are associated.Methods:Eight men aged between 55 and 65 years were evaluated, all suffering from cerebrovascular injury and with hemiparesis for at least six months. The following evaluations were performed: 1) echocardiography to evaluate systolic cardiac function; 2) Record the heart rate (HR) and RR intervals (RRI), beat by beat, to assess neural control of the heart. These data were analyzed in the frequency domain, by means of spectral analysis of the following components: high frequency, low frequency and LF/HF ratio. The Pearson correlation test was applied (p ≤0.05).Results:Demographic. anthropometric and physiological characteristics: Age = 58.62 ± 2.88 years; BMI = 27.41 ± 5.33 kg/m2; LF = 61.78 ± 26.79 (un); HF = 38.23 ± 26.79 (un); LF/HF = 3.41 ± 3.38; EF = 0.65 ± 0.04. There was no statistically significant correlation between the spectral indices of low (LF) and high frequency (HF) with stroke volume and the presence of risk factors for CVA.Conclusion:In the present study, the stroke volume of the left ventricle is normal and the neural control of the heart may be normal or not, even in the presence of risk factors for CVA.